An investigation of schema theory applied to the biomechanics of the sprint start in athletics - Darragh G.; Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Schmidt's schema theory (1975) predicts that variable practice (VP) will outperform constant practice (CP). The implications of this for the teaching of skills such as the sprint start are that VP should allow equal or better learning to CP. The aim of this study was to examine the effect on novice subjects of practicing with varying block settings on the learning of the sprint start. A deterministic model of the spint start was derived using the guidelines of Hay and Reid (1982) to identify factor likely to affect performance. Measures of the factors were obtained using video and laser analysis. The affect of VP and CP on these factors was evaluated using a pre, post retention expermental design. Performance of the sprint start was compared between VP (n=6), CP (n=5), and Control (n=5) groups. Results showed no significant difference (p<0.05) between the VP and CP groups, as both groups improved to the same extent.